Molecular and structural monitoring of epithelial mesenchymal in breast tissue / Siti Norbaini Sabtu - Siti Norbaini , Sabtu (2021)
The epithelial mesenchymal transition (EMT) is a crucial process in cancer progression and metastasis. Study of metabolic changes during the EMT process is important in seeking to understand the biochemical changes associated with cancer progression, not least in scoping for therapeutic strategies aimed at targeting EMT. Raman spectroscopy and synchrotron small angle x-ray scattering (SAXS) were used herein to study the metabolic changes associated with EMT in human breast cancer tissue. For Raman analysis, tissue from 23 patients were collected, comprising non-lesional, EMT and non-EMT breast cancer samples. Analysis was made in the fingerprint Raman spectra region (600 -1800 cm-1). Multivariate analysis involving Independent Component Analysis (ICA), Principal Component Analysis (PCA) and Non-Negative Least Square (NNLS) were used to analyse the Raman spectra data. The results show significant differences between EMT and non-EMT cancers in lipid, protein, and nucleic acids. Using SAXS techniques, structural components of the tissues were examined at momentum transfer values between q = 0.2 nm-1 and 1.5 nm-1. From the SAXS patterns, axial d-spacing and diffuse scattering intensity were observed to provide the greatest discrimination between the various tissue types. The overall intensity of scattering from cancerous regions is a degree of magnitude greater in cancer-invaded regions.Present results indicate that as aids in tissue diagnosis SAXS are capable of distinguishing areas of invasion by disease as well as delivering further information at the supramolecular level.